PENGARUH KEPEMILIKAN INSTITUSIONAL, DEWAN KOMISARIS INDEPENDEN, KUALITAS AUDIT, KOMITE AUDIT, KARAKTER EKSEKUTIF, DAN LEVERAGE TERHADAP TAX AVOIDANCE (Studi Empiris Pada Perusahaan Manufaktur di Bursa Efek Indonesia dengan Tahun Pengamatan 2010-2014) - Ayu Feranika; Mukhzarudfa; Tona Aurora L (Magister Ilmu Akuntansi Universitas Jambi, 2016)
This study aims to determine the effect of the ownership institutional, independentdirectors, quality audit, the committee audit, executive character and leverage of the tax avoidance at the companies listed in the Indonesia Stock Exchange Period 2010-2014. The population in this study is a manufacturing company in BEI. The sampling technique using purposive sampling. The data analysis technique used is by using multiple regression. Statistical hypothesis testing using the F and statistical test t. The results showed that : (1) the ownership institutional, independent directors, quality audit, the committee audit, executive character and leverage simultaneously on tax avoidance, (2) ownership institutional effect on tax avidance, (3) independent directors effect on tax avoidance, (4) quality audit affect on tax avoidance , (5) committe audit not effect on tax avoidance, (6) executive character affect on tax avoidance, (7) leverage not effect on tax avoidance.